재직자 직업훈련 관련 공적재정의 구조와 성과: 효과 분석 - 이철인 (12096, 2011)
This paper examines how the levy-grant system for on-the-job training affects individual workers' training level and the subsequent wage growth. Some notable results include: (i) the workers at the firms facing high net benefits (i.e., grant minus levy) r